Methanol and Sorbitol Affect the Molecular Dynamics of Arginine Deiminase: Insights for Improving its Stability - Zarei, Mahboubeh; Sabetian, Soudabeh; Rahbar, Mohammad Reza; Negahdaripour, Manica (Current Proteomics, 2022)
Background: The arginine deiminase enzyme of Mycoplasma arginini (MaADI) is a potential anti-cancer agent for treating arginine-auxotrophic cancers. Investigating the protein stability in the presence of osmolytes can help to increase protein stability under various stressed conditions. Methods: In this study, the stability and dynamics of MaADI were investigated in pure water and solutions of 1 M sorbitol, 10% (v/v) methanol, and 50% (v/v) methanol using molecular dynamics simulation. Results: Sorbitol was found to stabilize the protein, whereas high-concentrated methanol destabilized it. Sorbitol molecules interacted with the protein through hydrogen bonding and reduced the protein fluctuations. At 50% methanol, the flexibility of regions 4-8, 195-201, 314-324, and 332- 337 in the MaADI was increased, whereas residues 195-201 showed the highest variations. Conclusion: Thus, these regions of MaADI, especially 195-201, are the most sensitive regions in the presence of denaturing agents and can be subjected to protein engineering to improve the stability of MaADI.
Keywords: methanol